2020
DOI: 10.1039/d0cc04036c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiO2−x/W18O49 hollow double-shell and core–shell microspheres for CO2 photoreduction under visible light

Abstract: The fabrication of core–shell and double-shelled hollow microspheres of W18O49 (blue) and self-assembled TiO2−x for enhanced CO2 photoreduction to CO under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Notably, the merits of a narrow band gap, fast charge migration, and outstanding light absorption capacity endow tungsten oxide (WO 3– x ) as a suitable candidate for constructing a heterojunction with g-C 3 N 4 . W 18 O 49 , with plentiful W 5+ defects and oxygen vacancies, can broaden the wavelength range of light absorption, indicating that more electrons can be excited. , In previous work, core–shell microspheres of TiO 2– x /W 18 O 49 were prepared via a solvothermal treatment and the presence of W 18 O 49 could enhance the optical capturing range of this composite . In another report, W 18 O 49 /TiO 2 photocatalysts were obtained by Huang et al and showed outstanding activity.…”
Section: Introductionmentioning
confidence: 98%
“…Notably, the merits of a narrow band gap, fast charge migration, and outstanding light absorption capacity endow tungsten oxide (WO 3– x ) as a suitable candidate for constructing a heterojunction with g-C 3 N 4 . W 18 O 49 , with plentiful W 5+ defects and oxygen vacancies, can broaden the wavelength range of light absorption, indicating that more electrons can be excited. , In previous work, core–shell microspheres of TiO 2– x /W 18 O 49 were prepared via a solvothermal treatment and the presence of W 18 O 49 could enhance the optical capturing range of this composite . In another report, W 18 O 49 /TiO 2 photocatalysts were obtained by Huang et al and showed outstanding activity.…”
Section: Introductionmentioning
confidence: 98%
“…[17][18][19][20] Among them, heterojunction construction is proved to be an effective strategy due to the efficient transfer and separation of photogenerated charge carriers. [21][22][23] The preparation processes of hierarchical TiO 2 @ZnIn 2 S 4 coreshell hollow spheres (CSHS) are illustrated in Figure 1a. Firstly, SiO 2 spheres with average diameters of 350 nm as the hard-templates are prepared by a modified Stöber method (Figure S1a, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the synthesis of inorganic nanomaterials has been explored with a view to the nature of precursors, the structures and properties of products as well as the feasibility and simplification of methods. For instance, Sun et al successfully prepared GdMnO 3 material using a typical sol-gel method and subsequently in-situ generated GdMn 2 O 5 /GdMnO 3 materials by acid treatment for oxygenated VOC complete oxidation; [ [51] Deng and coworkers fabricated TiO 2 supported Pt nano-/single-atom-catalyst by using the molten salt method, and 0.2 wt% Pt catalyst showed high catalytic activity for toluene removal. [52] Our team once created superparamagnetic ferroferric oxide nanoparticles by coprecipitation method, and then yielded hydrophilic or hydrophobic targeting biomaterials by a few modifications.…”
Section: Synthesis Of Inorganic Nanomaterialsmentioning
confidence: 99%